Genetic Variants Associated With Response to Platinum-Based Chemotherapy in Non-Small Cell Lung Cancer Patients: A Field Synopsis and Meta‐Analysis - Hilary Sito; Mohamad Ayub Khan Sharzehan; Md Asiful Islam; Shing Cheng Tan (Frontiers Media S.A., 2024)
Background: Publications on the associations of genetic variants with the response to platinum-based chemotherapy (PBC) in NSCLC patients have surged over the years, but the results have been inconsistent. Here, a comprehensive meta-analysis was conducted to combine eligible studies for a more accurate assessment of the pharmacogenetics of PBC in NSCLC patients.Methods: Relevant publications were searched in PubMed, Scopus, and Web of Science databases through 15 May 2021. Inclusion criteria for eligible publications include studies that reported genotype and allele frequencies of NSCLC patients treated with PBC, delineated by their treatment response (sensitive vs. resistant). Publications on cell lines or animal models, duplicate reports, and non-primary research were excluded. Epidemiological credibility of cumulative evidence was assessed using the Newcastle-Ottawa Scale (NOS) and Venice criteria. Begg's and Egger's tests were used to assess publication bias. Cochran's Q-test and I2 test were used to calculate the odds ratio and heterogeneity value to proceed with the random effects or fixed-effects method. Venice criteria were used to assess the strength of evidence, replication methods and protection against bias in the studies.Results: A total of 121 publications comprising 29,478 subjects were included in this study, and meta-analyses were performed on 184 genetic variants. Twelve genetic variants from 10 candidate genes showed significant associations with PBC response in NSCLC patients with strong or moderate cumulative epidemiological evidence (increased risk: ERCC1 rs3212986, ERCC2 rs1799793, ERCC2 rs1052555, and CYP1A1 rs1048943; decreased risk: GSTM1 rs36631, XRCC1 rs1799782 and rs25487, XRCC3 rs861539, XPC rs77907221, ABCC2 rs717620, ABCG2 rs2231142, and CDA rs1048977). Bioinformatics analysis predicted possible damaging or deleterious effects for XRCC1 rs1799782 and possible low or medium functional impact for CYP1A1 rs1048943.Conclusion: Our results provide an up-to-date summary of the association between genetic variants and response to PBC in NSCLC patients.